REPRESENTASI JURNALISME VISUAL DALAM INFOGRAFIS TIRTO.ID KASUS REYNHARD SINAGA - Tazkiya Alisha (2020)
The press is always oriented towards the public, which means that the press plays a very important role in shaping public opinion and influencing people's behavior. Sexual violence is one of the most complex cases in Indonesia, this is because the legal umbrella is still very limited in looking at cases of sexual violence. In the legal case for sexual violence that ensnared Reynshard Sinaga, namely Indonesian citizens in England, it became a turning point or a reflection of Indonesian law. Laws that are able to accommodate forms of sexual violence are not only limited to the penetration of men and women. This research discusses the meaning contained in the infographic @tirtoid edition 'If the Reynhard Case Happens in Indonesia' on the meaning manifestation represented by the audience. This research is analyzed by using Kress and Leeuwen's concept of social semiotics to analyze the semiotic text contained in the @tirtoid infographic using four key dimensions of social semiotics, namely discourse, genre, style, and modality. The approach used in this research is a qualitative approach with descriptive methods. The researcher concluded that the infographic is a product of participatory culture and the meaning contained in the @tirtoid infographic has the effect of increasing audience awareness about sexual violence that is not sexually oriented, and also victim-blaming as if it has become a culture. This can be seen from the audience response in the comments column.